PELAKSANAAN PERSONAL HYGIENE CHEF DI FOUR POINTS BY SHERATON BATAM KEPULAUAN RIAU - Arba Yanti; Andi M Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Kitchen is a food processing center in the hotel. Good or bad food products produced in hotels depend on the cleanliness or personal hygiene of a chef in processing a food ingredient. Personal hygiene is an individual's effort to maintain health by taking care of personal hygiene, appearance and environment. To produce healthy and clean food, a chef's personal hygiene really needs to be considered because it will have an impact on the food to be served. This study aims to determine the application of personal hygiene chefs at Four Points By Sheraton Batam, Riau Islands. This study uses a qualitative method with a descriptive approach, where the data obtained is analyzed based on the researcher's ability to relate information, facts and data by presenting observations, interviews and documentation and is an analysis of the problems found in the field, so that a clear picture of the object can be obtained. researched and can draw clear conclusions. The results of this study indicate that the implementation of the Personal Hygiene Chef at the Four Points By Sheraton Batam Riau Islands is not fully in accordance with the standard operating procedures at the hotel. Keyword : Kitchen, Personal Hygiene, Chef, Hotel.